Penerapan Speech Recognition Pada Aplikasi Mobile Kamus Bahasa Sasak - Yuliadi Yuliadi; Mohammad Taufan Asri Zaen; Rusdan Rusdan; Rodianto Rodianto; Yunanri W (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Language is an important part of a country or region in communicating between individuals formally and informally. However, it becomes an obstacle, not all outsiders and native residents of Lombok Island (Sasak Ethnic) understand the dialect of Sasak, Lombok Island, West Nusa Tenggara. In addition, in formal and informal meetings, it is rare to use the Sasak language in communicating. Based on these problems we need a media that helps in interacting in the form of a dictionary. The Sasak Language Dictionary is presented in a mobile-based application by utilizing voice as input which is known as Speech Recognition technology. The application is built using a prototype methodology and programming tools using Embarcadero Delphi 10.32 Programming. and SQLite as database. The result of this study is to build a Sasak Language Dictionary mobile application using Speech Recognition in the form of utilizing voice as input.